Walking the tight rope- balancing private property rights of individuals and the right to housing of informal settlers - Matu, Doris Wanjiru (Strathmore University, 2016)
The purpose of this research is to show the conflict that arises between the right to property for owners of land and the right to housing of the informal settlers on these lands. The main objective of this research is to investigate the concept of illegal forced evictions and the legal framework that surrounds the practices that render such evictions against the principle of human dignity and the right to accessible and adequate housing in the context of informal settlements. There will be an attempt to show cause for the current homelessness situation that has been brought about by past and present irregular and illegal land allocation.The research method used is the doctrinal research method which involves itself with the analysis of legal rules and formation of doctrines. The framework that regulates forced evictions in Kenya and the right to housing in the informal settlement sector has been investigated and the obligations of the state with regards to the right to housing and the protection of prope1ty analyzed.This research has come to the conclusion that a lot remains to be done to change the culture of impunity that is usually the case during evictions. Too many rights are violated. Too many people are injured and humiliated. They are in desperate need of a court system that can correct the imbalance that seems to favor the right to prope1ty. There is a need to come up with solutions that are innovative and that can lead to justice and positive transformation of society.
A dissertation presented in partial fulfilment of the Bachelor of Laws degree Strathmore Law School, Strathmore University